Resource management and contours of development : reflections through macro-micro narratives - Barik, B. C. (Jaipur : Rawat Publications, 2000)
Outcome of papers presented at the National Seminar on "Common Property Resources and Planned Development in Western India: Challenges and Prospects," held during January 19-21, 1999, at Nanded.
Includes bibliographical references and index.
Keywords: MANAGEMENT; SUSTAINABLE DEVELOPMENT; CONSERVATION OF NATURAL RESOURCES